Diagnosis of chronic thromboembolic pulmonary hypertension: A Canadian Thoracic Society clinical practice guideline update. Issue 4 (2nd October 2019) - Helmersen, Doug; Provencher, Steeve; Hirsch, Andrew M.; Van Dam, Anne; Dennie, Carole; De Perrot, Marc; Mielniczuk, Lisa; Hirani, Naushad; Chandy, George; Swiston, John; Lien, Dale; Kim, Nick H.; et al.
Abstract: BACKGROUND: An important and common cause of pulmonary hypertension (PH) is chronic thromboembolic PH (CTEPH). Many care gaps exist in the evaluation of CTEPH including lack of awareness of the diagnosis, failure of clinicians to routinely consider CTEPH in patients at risk, and misguided diagnostic assessment practices including those which may be incomplete or unnecessary. METHODS: A representative multidisciplinary panel of expert physicians undertook a formal clinical practice guideline development process. A total of 4 key clinical issues were defined according to the Patient/problem, Intervention, Comparison, Outcome (PICO) approach. The panel performed an evidence-based, systematic literature review, assessed and graded the relevant evidence, and made 4 recommendations. RESULTS: Patients should not be routinely screened for the presence of CTEPH (using echo or pulmonary vascular imaging) following an acute pulmonary embolism (PE). Risk factors for CTEPH following acute PE have been established, and patients in these higher risk groups may merit closer attention during clinical follow-up. Routine screening for CTEPH following acute PE has not yet been demonstrated in prospective controlled trials to improve patient outcomes. In patients with PH, clinicians should perform nuclear ventilation/perfusion (V/Q) lung scanning as initial testing to rule out CTEPH. Either planar or single photon emission computed tomography (SPECT) V/Q are acceptable forms of V/Q lung scanning. A normal perfusion scan effectively rules out the possibility of CTEPH. A negative computed tomography pulmonary angiogram (CTPA) does not rule out CTEPH. In patients with suspected CTEPH, CTPA should be performed to confirm the presence and assess the anatomic extent and location of chronic thromboembolic material. A positive CTPA, confirming chronic thromboembolism, should prompt referral to an expert PH centre where a formal diagnosis can be established. A negative, indeterminate or technically poor CTPA does not exclude CTEPH and should also prompt referral to an expert PH centre for further testing. Magnetic resonance pulmonary angiography is not currently recommended for routine assessment in patients with suspected CTEPH. DISCUSSION: The foundation of CTEPH diagnosis remains clinicians' consideration of this possibility in patients at risk. Future research is required to identify the specific diagnostic tests and/or algorithms which will perform best in formal screening protocols for CTEPH. The current diagnosis of CTEPH will until then continue to rely on clinician led case finding, with diagnostic investigations arranged during the course of clinical care. Once case finding investigations have been initiated, an approach which follows the recommendations and sequence of testing outlined in this guideline may improve the rate of diagnosis of CTEPH and potentially the outcomes in these patients. This guideline will be reviewed every three years or sooner, in accordance with the Canadian Thoracic Society Living Guideline Model.